Pulmonary Vein Isolation With Very High Power, Short Duration, Temperature-Controlled Lesions: The QDOT-FAST Trial - Reddy, V Y.; Grimaldi, M.; Potter, T.; Vijgen, J M.; Bulava, Alan; Duytschaever, M F.; Martinek, M.; Natale, A.; Knecht, S.; Neužil, P.; Purerfellner, H. (Elsevier Science Inc, 2019)
Objectives: This study sought to evaluate the safety and short-term performance of a novel catheter for very high power–short duration (vHPSD) ablation in the treatment of paroxysmal atrial fibrillation. Background: The vHPSD catheter is a novel contact force–sensing catheter optimized for temperature-controlled radiofrequency ablation with microelectrodes and 6 thermocouples for real-time temperature monitoring; the associated vHPSD algorithm modulates power to maintain target temperature during 90 W, 4 s lesions. Methods: QDOT-FAST (Clinical Study for Safety and Acute Performance Evaluation of the THERMOCOOL SMARTTOUCH SF-5D System Used With Fast Ablation Mode in Treatment of Patients With Paroxysmal Atrial Fibrillation) is a prospective, multicenter, single-arm study enrolling patients with symptomatic paroxysmal atrial fibrillation indicated for catheter-based pulmonary vein isolation. Primary endpoints were short-term effectiveness (confirmation of entrance block in all targeted pulmonary veins after adenosine/isoproterenol challenge) and short-term safety (primary adverse events). Participants were screened for silent cerebral lesions by magnetic resonance imaging. Patients were followed for 3 months post-ablation. Results: A total of 52 patients underwent ablation and completed follow-up. Pulmonary vein isolation was achieved in all patients using the study catheter alone, with total procedure and fluoroscopy times of 105.2 ± 24.7 min and 6.6 ± 8.2 min, respectively. Most patients (n = 49; 94.2%) were in sinus rhythm at 3 months. Two primary adverse events were reported: 1 pseudoaneurysm; and 1 asymptomatic thromboembolism. There were no deaths, stroke, atrioesophageal fistula, pulmonary vein stenosis, or unanticipated adverse device effects. Six patients had identified silent cerebral lesions—all classified as asymptomatic without clinical or neurologic deficits. Conclusions: This first-in-human study of a novel catheter with optimized temperature control demonstrated the clinical feasibility and safety of vHPSD ablation. Procedure and fluoroscopy times were substantially lower than historical standard ablation with point-by-point catheters.
Keywords: atrial; fibrillationcatheter ablationcontact forceirrigation ratemicroelectrodepulmonary vein ablation